User acquisition and profile of COVID-19’s health education website: a descriptive study - Avinindita Nura Lestari; Tiara Putri Leksono; Reyfal Khaidar; Ekky Novriza Alam; Lutfan Lazuardi (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2020)
In early of 2020, China had identified a new etiology of pneumonia which was later called Coronavirus Disease 2019 (COVID-19) by the World Health Organization (WHO) and the condition declared as pandemic. In this emergency state of affair, people will seek information from websites disseminating health information online, including Indonesia. Since there is currently no vaccine or specific antiviral treatment, the application of preventive measures has been essential. The hygiene and health measures can be easily spread widely as there’s been fast & numerous information spreading in the media, but that is not usually the case with underprivileged people with little access to technology. False news and lack of credible sources are also a threat. A health startup in Bandung, Indonesia, made initiatives to educate people about COVID-19 prevention through downloadable script and audio in the form of Public Service Announcement provided with 19 local languages through their website. This study aims to know the characteristics of profile users accessing the website through descriptive observational approach. The data came from the website automatically analysed by Google Analytics. We look into the audience data, comprising demographics and geographical distribution. Additionally, we observe the acquisition data that helps us in seeing website traffic. The significant difference found in this study is seen in the age group, meanwhile the gender group did not have a significant difference, which has 8% of disparity. By geographical distribution, 60% of top users are located in cities located in Java Island. Direct traffic, interestingly, made up almost 86 percent of all traffic. Twitter ranked the top for the social media traffic in our case. In conclusion, it is necessary to promote credible information in COVID-19 preventive measures and help maintain the accessibility of information.